Bringing Relationships into Voice Hearing - Allison, Rob; Lafferty, Ruth (Taylor & Francis, 2025)
This book presents a novel, theoretically informed practical approach to voice hearing, which aims to help readers improve relational harmony, reduce distress related to voice hearing, and improve experiences of supportive approaches.